Tinjauan Yuridis Sanksi bagi Pelaku Tindak Pidana Pencurian dengan Kematian dalam Konteks Sistem Hukum Indonesia - Muhammad Ridwan Lubis (Mahesa Research Center, 2023)
This study evaluates the phenomenon of vigilantism in Indonesia, focusing on the juridical aspects of sanctions against perpetrators of criminal theft resulting in death. The research reveals that the current criminal regulations related to vigilantism, as outlined in Articles 170, 351, 406, and 338 of the Indonesian Criminal Code (KUHP), have not fully provided decisive penalties. Analysis of the verdict in Decision Number 8/Pid.B/2018/PN. Bks indicates that the perpetrator was charged under Article 170 paragraphs (1) and (2) jo Article 55 paragraph (1) of the KUHP, receiving an 8-year prison sentence for vigilantism leading to death. Despite the verdict being based on the fulfillment of the elements of the charges, the research asserts that law enforcement against vigilantism has not yet demonstrated its effectiveness. In this context, there is a need for a legal process more aligned with justice and legal certainty for the victims. The research methodology employed is Normative Juridical, utilizing secondary data and expert interviews. The findings highlight the importance of effective law enforcement against vigilantism that meets the elements of Article 170 or 351 of the KUHP to achieve justice for the victims.